2016
DOI: 10.4081/ejh.2016.2605
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional compensation of masseter muscles in unilateral posterior crossbite patients

Abstract: Unilateral posterior crossbite is a widespread, asymmetric malocclusion characterized by an inverse relationship of the upper and lower buccal dental cusps, in the molar and premolar regions, on one side only of the dental arch. Patients with unilateral posterior crossbite exhibit an altered chewing cycles and the crossbite side masseter results to be less active with respect to the contralateral one. Few studies about morphological features of masticatory muscle in malocclusion disorders exist and most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
3
16
0
1
Order By: Relevance
“…For the detection of images, Laser Argon (458 e 488 nm) was utilized. All images were digitized at a resolution of 8 bits into an array of 2048 × 2048 pixels [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the detection of images, Laser Argon (458 e 488 nm) was utilized. All images were digitized at a resolution of 8 bits into an array of 2048 × 2048 pixels [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The size of the biological response depends on the application time, force magnitude and force distribution [ 3 ]; in fact, different force distribution patterns could determine different type of tissue reactions. By that, several studies focused on evaluating tissue reaction to force appliance [ 4 , 5 ] and iatrogenic sequelae to orthodontic force have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…Piancino et al [ 1 ] have shown by electromyography that when chewing on the crossbite side, the ipsilateral masseter presents a reduced activity, while on the contralateral side, the masseter contractile activity is unaltered or increased. Our previous morphological investigations have shown in contralateral masseter an increase in muscle proteins, as sarcoglycans and integrins, and an increase in number of myonuclei and satellite cells, if compared to the ipsilateral one [ 9 ]. Satellite cells are muscle stem cells interposed between the sarcolemma and the basement membrane of the muscle fibres; these are cells in a quiescent state [ 27 ], but they are induced to proliferate by injury or by increased muscle activity [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little morphological data exist on masticatory muscles during crossbite disease, and most of them have been performed on animal models [ 5 , 6 , 7 ]. Our morphological investigations, performed on humans, have demonstrated—in contralateral muscles—an increased thickness of muscle fibres and an increase in integrins and sarcoglycan expression [ 8 , 9 ]. Integrins are proteins that guarantee a correct muscular development during somitogenesis [ 10 , 11 ], and sarcoglycans are transmembrane glycoproteins that play a key role in sarcolemma stabilization during muscle contraction [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%